2023
DOI: 10.3390/app132212465
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Treatment via Microwave Radiation Improves Viscoelastic Properties of Native Gluten-Free Flours for Extrusion 3D Printing

Tetiana Lisovska,
Karol Banaś,
Agnieszka Orkusz
et al.

Abstract: The market for gluten-free products is experiencing significant growth due to the increase in the number of gluten/wheat affected patients diagnosed, but largely as a result of the emergence of a new niche market dedicated for consumers who optionally avoid gluten. Native flours are perceived as viable alternative for industrially used starch and hydrocolloids blends, mainly due to their lack of vitamins and minerals, which are abundant in non-refined raw materials. Edible inks for on-demand printing are under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Microwave-assisted heat-moisture treatment (MW-HMT) has been found to impact the nutritional profile of flours. Studies have shown that microwave heating can enhance the functional properties of flours, such as water holding, oil binding, emulsifying, and foaming capacities, as well as protein solubility [16][17][18][19][20][21]. Furthermore, microwave-assisted dry-heat and heat-moisture treatments have been shown to modify the techno-functional properties and gel viscoelasticity of rice flour, with effects varying depending on the moisture content of the flour [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-assisted heat-moisture treatment (MW-HMT) has been found to impact the nutritional profile of flours. Studies have shown that microwave heating can enhance the functional properties of flours, such as water holding, oil binding, emulsifying, and foaming capacities, as well as protein solubility [16][17][18][19][20][21]. Furthermore, microwave-assisted dry-heat and heat-moisture treatments have been shown to modify the techno-functional properties and gel viscoelasticity of rice flour, with effects varying depending on the moisture content of the flour [22,23].…”
Section: Introductionmentioning
confidence: 99%